دور الإدارة الالكترونية في تعزيز الشفافية بالإدارة المحلية - مناصر, شهرزاد; حاحة, عبد العالي (جامعة الوادي University of Eloued, 2019)
من ابرز أسباب انتشار الفساد الغموض وانعدام الشفافية، فالشفافية في أعمال الإدارة تعد وبحق الطريق إلى التنمية والإصلاح الإداري، ولقد لقيت جهود وبرامج تقوية الشفافية الإدارية ومكافحة الفساد الإداري اهتماما كبيرا على المستوى الوطني، لذا سعت الدولة لاستغلال التقدم التكنولوجي الحاصل وتوظيف وسائل الاتصال الحديثة وتكنولوجيا المعلومات في مكافحة الفساد وتجسيد الشفافية داخل الإدارة المحلية، فأصبح لزاما اليوم على كافة الإدارات المحلية خوض معركة التطوير والتحسين والتحديث وتوظيف التقدم التكنولوجي والمعلوماتي في دفع عجلة التنمية ومحاربة الفساد وتحسين الخدمات. Abstract: One of the Most causes of corruption is the ambiguity and the absence of transparency in the work of the administration, as a matter of fact transparency is the right path to development and administrative reform also, many Efforts and programs had received great attention at national level used to strengthen administrative transparency and combat administrative corruption, Therefore, the State has sought to exploit the technologicalachieved progress and employ the modern means of communication and information technology In order to fight against corruption and the enhancement of transparency within the local administration, it became imperative today to all local administrations to strugglefor the development, improvement and modernization in addition to the use of technological progress and information in advancing the development, improving services and fighting corruption.
Keywords: الإدارة الالكترونية ; الشفافية الإدارية ; الإدارة المحلية